Local excitons in Si/Ge inverted quantum huts (IQHs) embedded Si. (5th August 2021) - Dey, Arka Bikash; Sanyal, Milan K; Patil, Swapnil; Ali, Khadiza; Biswas, Deepnarayan; Thakur, Sangeeta; Maiti, Kalobaran
Abstract: We investigate the properties of excitons in the SiGe inverted quantum huts (IQHs) embedded in Si employing high-resolution x-ray photoemission spectroscopy. Ultra-small Si/Ge IQHs (13.3 nm × 6.6 nm) were grown on a Si buffer layer deposited on a Si (001) substrate using molecular beam epitaxy. We study the behavior of the excitons at different depths of the IQH structures by exposing the desired surfaces via controlled sputtering and annealing processes. The Si and Ge core level spectra show interesting properties at different surfaces; additionally, we discover distinct new features at the lower binding energy side of the Ge 3 d peak. The emergence of these features is attributed to the final state effects arising from core hole screening by the excitons. The properties of these features in the spectra collected at different locations of the IQHs are found significantly different from each other, indicating the local character of the excitons. These results provide a pathway to study the properties of excitons in such quantum structures. The evidence of the local character of the excitons suggests a type I behavior of the system, which is important for the devices for optoelectronic applications, quantum communications, etc.